The Relationship Between Service Quality, Perception of Expediency with The Decision of Go-Ride Service Users in Makassar - Ernawati Ernawati; Andi Maulani Muchtar; Vebby Anwar; Norhaedah Norhaedah (PT. Publikasiku Academic Solution, 2023)
This study aims to analyze the relationship between service quality, perceived utility, and the choices made by go-ride service users in Makassar. The theories used in this study are the service decision theory developed by Kotler and Keller, Davis’s theory of perceived usefulness, and Kotler’s theory of service quality. 50 Makassar go-ride service users were given questionnaires as part of the quantitative study methodology. The Pearson product-moment correlation approach is the one employed for data analysis. The study finds findings that decisions about which services to employ are positively and significantly correlated with both service quality and perceived usefulness.